Pengaruh Pembelajaran Discovery Berbantuan Media Laboratorium Virtual Terhadap Kemampuan Pemecahan Masalah Fisika Peserta Didik - Putri Iman Sari; Gunawan Gunawan; Ahmad Harjono; Hairunnisyah Sahidu (Indonesian, 2022)
Problem-solving ability is an essential competency that should be developed in physics learning. However, conventional teacher-centered instruction has limited students' opportunities to develop this ability effectively. This study aimed to analyze the effect of the Discovery Learning model assisted by a virtual laboratory on students' physics problem-solving ability. This research employed a quasi-experimental method using a Pre-test and Post-test Control Group Design. The samples were selected through cluster random sampling, resulting in one experimental class receiving Discovery Learning assisted by a virtual laboratory and one control class receiving conventional instruction. Data were collected using a validated essay-based physics problem-solving test. The data were analyzed descriptively and inferentially using the pooled variance t-test after satisfying the assumptions of normality and homogeneity. The results revealed that the students' physics problem-solving ability in the experimental class was higher than that of the control class. The hypothesis testing further indicated that the implementation of Discovery Learning assisted by a virtual laboratory had a significant positive effect on students' physics problem-solving ability. Therefore, this instructional model can be considered an effective alternative for enhancing students' physics problem-solving ability.